Multi-storey timber buildings in practice - A study on how to practically use timber as a structural material - Söderberg, Martin; Kronberg, Rasmus (My University, 2020)
During the latest years, the movement towards sustainable solutions have truly influenced the debate around the building industry. Many of the stakeholders have started to show an interest in reducing emissions. One way of doing this could be by using timber instead of the traditional steel and concrete in multi-storey buildings. However, as the previous use of timber in larger structures have been limited, there is a gap of knowledge and experience in the industry on how to practically implement timber in the design of multi-storey buildings. The purpose of this study is therefore to investigate, gather information and give example on how timber can successfully be used as a structural material. This to facilitate the implementation of timber early in the design process. The study is done in three steps. First, a review is done on what timber systems that different manufacturers offers, together with the solutions used in some of the latest years new ground-breaking timber buildings. The second step is a case study where timber concepts are developed for two different projects, previously built in concrete/steel. In the last part, preliminary design tools are developed for some of the structural elements studied throughout the project. The study shows that there are several interesting systems and products that already have been used in multi-storey timber building projects. Systems based on CLT and LVL have come very far and are available on the market in Sweden. The study also shows that there could be a large upside on using timber for buildings where a low structural self-weight is desired, for instance in areas with difficult soil conditions or when adding an extra storey on top of an existing structure. On the other hand, a too light-weight building could be problematic in terms of global stability against tilting. This call for solutions where combinations of materials are used in a wise manner. Here, the development of timber-concrete composites has a large potential and is already used in some projects abroad. But it is still associated with uncertainties regarding some of the technical questions on how to calculate and design, so it will probably be a few years before this technique will have its break-through on the commercial market in Sweden.
Keywords: Timber; multi-storey building; structural system; preliminary design; sizing diagrams; timber materials; TCC; hybrid structure